Data Communication Network and its Delay Effect on the Dynamic Operation of Distributed Generation Units in a Microgrid - Setiawan, M.; Shahnia, Farhad; Chandrasena, R.; Ghosh, Arindam (Institute of Electrical and Electronics Engineers (IEEE), 2014)
A three-level hierarchical control system is considered for microgrids. The microgrid central controller receives the desired ratio for the output power of the available distributed generation units (DG) from the network tertiary controller. It then passes this information to the primary controller of each DG in the form of setpoints. In addition, the central controller receives some information from the DGs or the network and considers them to adjust the setpoints for the DGs. In this paper, the effect of the data transfer delays in the communication system of future microgrids is investigated on the dynamic operation of the distributed energy resources.